ASSESSMENT OF THE ROLE OF THE MASS MEDIA IN PREVENTION OF ENVIRONMENTAL POLLUTION AMONG RESIDENTS OF ETSAKO WEST LOCAL GOVERNMENT, EDO STATE - Chukwuebuni, Florence Oghenekome; Awoviebe, Joy; Isah, Abdulazeez; Ogerugba, Isaac Usiwo (African Journal of Social and Behavioural Sciences, 2023)
Environmental pollution and degradation have constituted a bane to the development of Nigeria. The media have been seen to be an important tool in creating awareness, informing and educating the public. However, this study examined the role of the mass media in prevention of environmental pollution among residents of Etsako West Local government Area of Edo State. The survey approach was used for this study and questionnaire was used as the instrument for data collection. A sample size of 400 respondents was taken for the study and data from the questionnaire were analysed in frequency tables and simple percentages. The study was anchored on Agenda setting theory. Findings however revealed that the mass media have not been carrying out environmental campaign/communication. The study also found out that media's extensive involvement in environmental campaigns suggests that they have the power to set the agenda and prioritise environmental issues in public discourse. It therefore recommends that, Mass media should engage more in environmental communication, advocacy campaign to address environmental issues in Nigeria.